Comparing the effect of in-person and virtual childbirth preparation trainings on the fear of childbirth (FOC) and pregnancy experience of pregnant women: protocol for a quasi-experimental feasibility study - Seyedeh Robab Mousavi (BMC, 2021)
Abstract Background Childbirth preparation trainings are an important component of prenatal education, and pregnant women are increasingly interested in seeking information from online sources. The aim of this study is to compare the feasibility and the effects of in-person and virtual childbirth preparation training courses on the pregnancy experience, fear of childbirth (FOC), birth preference, and type of delivery among pregnant women. Methods In total, 165 primiparous women referring to a prenatal clinic at Milad Hospital in Tehran, will be included in this study. The subjects will be selected using the convenience sampling method and will be divided into three groups of study A, study B, and control. The study groups A and B will receive virtual and in-person childbirth training with similar content, respectively. The control group will receive only routine prenatal care. In the 18th and 20th weeks of pregnancy, the demographic information, pregnancy experience scale (PES), and version A of the Wijma delivery expectancy/experience questionnaire (WDEQ-A) will be completed, and in the 36th and 38th weeks of pregnancy, the PES and WDEQ-A questionnaires, as well as birth preference form will be completed. The type of delivery will be recorded in the first few days of postpartum. Conclusion This quasi-experimental clinical trial will investigate the effect of virtual childbirth preparation training on primiparous women. The expected outcomes will include the difference in pregnancy experience measured by the brief version of PES, the difference in FOC measured by WDEQ-A, the birth preference, and the type of delivery. Trial registration IRCT.ir: IRCT20180427039436N2 ;